1997
DOI: 10.1364/ao.36.009437
|View full text |Cite
|
Sign up to set email alerts
|

State-of-strain evaluation with fiber Bragg grating rosettes: application to discrimination between strain and temperature effects in fiber sensors

Abstract: An optical rosette that incorporates fiber Bragg gratings as strain gauges has been designed, fabricated, and tested. We investigated it by measuring the state of strain of a thin plate as the test structure submitted to an increasing load in a four-point bending configuration and for various angular orientations. This device has also been successfully investigated as a self-temperature-compensated in situ uniaxial strain sensor without any angular dependence and with high accuracy in recovery analysis, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Therefore three independent strain measurements in three different directions along the plane are sufficient to determine the principal strain axes, as long as the strain measurements are arranged at convenient angles in order to have at least two linearly independent measurements. Based on the standard equations for strain rosettes [8], the local strain equation for each strain sensor can be written as: where ε X and ε Y are the principal strain axes, α is the deviation angle regarding the principal axis, and β is the relation between the angles for each strain gauge. Figure 4 shows the schematic representation of the general problem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore three independent strain measurements in three different directions along the plane are sufficient to determine the principal strain axes, as long as the strain measurements are arranged at convenient angles in order to have at least two linearly independent measurements. Based on the standard equations for strain rosettes [8], the local strain equation for each strain sensor can be written as: where ε X and ε Y are the principal strain axes, α is the deviation angle regarding the principal axis, and β is the relation between the angles for each strain gauge. Figure 4 shows the schematic representation of the general problem.…”
Section: Methodsmentioning
confidence: 99%
“…Different configurations in optical strain sensors have also been reported in literature [4][5][6][7]. In the scope of performing strain measurements with FBGs, Magne et al [8] demonstrated its application on the implementation of an optical strain rosette. Although, due to high losses in fibre curvature, the effective dimension of the rosette is not negligible as it is required for a precise strain measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter is the optical fibre photo-elastic coefficient, ℎ is the thermal expansion coefficients of the host material and is the thermo-optic coefficient [14]. The effect of the optical fibre to the overall specimen stiffness is very small, because the FBG cross section << specimen cross section.…”
Section: Embedded Fbg Response To Strain and Temperature Variationmentioning
confidence: 99%
“…Various complicated temperature-compensation methods have been proposed, such as the use of dual-wavelength superimposed FBG sensors [60], saturated chirped FBG sensors [61], and an FBG sensor rosette [35]. We chose a simpler method that involved the use of an isolated, strain-free FBG sensor to measure thermal effects.…”
Section: Temperature Compensationmentioning
confidence: 99%